The Psychology of Sustainability and Sustainable Development: Advancing Decent Work, Inclusivity, and Positive Strength-Based Primary Preventive Interventions for Vulnerable Workers - Di Fabio, Annamaria; Svicher, Andrea (Frontiers in Psychology, 2021)
This article discusses the contribution of the psychology of sustainability and sustainable development to the well-being of vulnerable workers. The psychology of sustainability and sustainable development is a current research area in the field of Sustainability Science. It deals with sustainability as a framework to recognize and integrate the value of the psychological approach in the construction of processes linked to sustainable development. Accordingly, the psychology of sustainability and sustainable development could provide sustainable development processes for the employment of vulnerable workers. The contribution starts with the definition of the coordinates of a sustainable development process for vulnerable workers, anchoring it to the principles of decent work, and inclusiveness. Subsequently, positive variables involved in the sustainable development processes and their relationship with decent work and inclusiveness are discussed. Moreover, positive healthy organizations are introduced as work environments capable to take care of the well-being also of vulnerable workers. Lastly, the applications of positive strengths-based primary preventive interventions for vulnerable workers are analyzed. Perspectives for further research and intervention are also examined.